Pengukuran Tingkat Kesehatan OPZ terhadap Aspek Keuangan dan Manajemen (Studi Kasus pada Lazismu Al Jihad Banjarmasin) - Mairijani; Putri, Eka Yunisa (P3M Politeknik Negeri Banjarmasin, 2024)
The purpose of this research is to assess the health of Lazismu Al Jihad in terms of financial and management aspects using the OPZ Health Index (IKOPZ) as the measurement tool. This descriptive research employs a quantitative approach, utilizing primary data from interviews and secondary data from Lazismu Al Jihad's 2022 financial reports. The analysis technique applied is the OPZ Health Index (IKOPZ), calculated through a multi-stage weighted index method. The research findings indicate that Lazismu Al Jihad achieved a rank of 2 in both financial and management aspects. This signifies that Lazismu Al Jihad demonstrates strong financial performance with high effectiveness and efficiency in managing ZIS funds, enabling growth. Additionally, Lazismu Al Jihad shows good governance quality, adequate risk management, and adherence to prevailing sharia principles. Overall, the study concludes that Lazismu Al Jihad's health level is categorized as good with a rank of 2, indicating effective organizational management.